Effect of GABA(B) receptor agonist SKF97541 on cortical and hippocampal epileptic afterdischarges - Fábera, Petr; Mareš, Pavel (Physiological research, 2014)
Activation of GABA(B) receptors leads to longer inhibitory postsynaptic potentials than activation of GABA(A) receptors. Therefore GABA(B) receptors may be a target for anticonvulsant therapy. The present study examined possible effects of GABA(B) receptor agonist SKF97541 on cortical and hippocampal epileptic afterdischarges (ADs). Epileptic ADs elicited by electrical stimulation of sensorimotor cortex or dorsal hippocampus were studied in adult male Wistar rats. Stimulation series were applied 6 times with 10- or 20-min interval. Either interval was efficient for reliable elicitation of cortical ADs but stimulation at 10-min intervals did not reliably elicit hippocampal ADs, many stimulations were without effect. SKF97541 in dose 1 mg/kg significantly prolonged cortical ADs. Duration of hippocampal ADs was not significantly changed by either dose of SKF97541 in spite of a marked myorelaxant effect of the higher dose. Our present data demonstrated that neither cortical nor hippocampal ADs in adult rats were suppressed by GABA(B) receptor agonist SKF97541. Proconvulsant effect on cortical ADs indicates a different role in these two brain structures. In addition, duration of refractory period for electrically-induced ADs in these two structures in adult rats is different.
Keywords: Electroencephalography; Male; Rats, Wistar; organofosforové sloučeniny; elektroencefalografie; mozková kůra; Pyramidal Cells; pyramidové buňky; mužské pohlaví; potkani Wistar; epilepsie; krysa rodu Rattus; Hippocampus; agonisté receptorů GABA-B; Animals; Organophosphorus Compounds; zvířata; Rats; Epilepsy; GABA-B Receptor Agonists; hipokampus; Cerebral Cortex